Dinoflagellaten-Zysten als Paläoumweltindikatoren im Spätquartär des Europäischen Nordmeeres - Baumann, Astrid (Univ. Bremen, 2007)
Dinoflagellate cysts, paleoceanography, paleoenvironment, Late Quaternary, Norwegian-Greenland Sea. - Dinoflagellate cysts have been investigated in nine short sediment cores as well as two long sediment cores from the Norwegian-Greenland Sea and the North Atlantic to reconstruct the surface water paleoenvironment of the last climatic cycle and the Holocene. Holocene sea-surface temperatures and salinities during summer and winter and the extent of sea-ice cover were reconstructed. On the Rockall Plateau, higher cyst concentrations indicating favourable conditions and increased productivity only occur during parts of stage 5, 4-2, and the Holocene. Only sparse occurrences of dinocysts have been observed in the Norwegian-Greenland Sea before 10000 yr BP. Later, high abundances of O. centrocarpum and N. labyrinthus indicate the increased inflow of relatively warm Atlantic. A change in dominance of these species as well as a distinct increase in cyst concentrations marks the onset of the recent circulation system. In the Norwegian Sea, O. centrocarpum dominates the assemblages since about 7000 yr BP, while assemblages in the Iceland and the Greenland Sea are more complex due to the influence of different surface currents. : thesis